Network meta-analysis of the effects of combined exercise and vitamin intervention on insulin resistance and related indicators in patients with type 2 diabetes - Deng, Fangquan; Ji, Yin; Kong, Haijun; Fu, Yebiao; Zhang, Hanqiao; Zhang, Junting (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to evaluate the effects of vitamin supplementation, exercise, and their combined interventions on insulin resistance and related outcomes in patients with type 2 diabetes (T2D). Additionally, it examined the dose–response relationships between vitamin dosage, exercise intensity, and improvements in insulin resistance.MethodsRelevant studies investigating the impact of vitamin supplementation and exercise interventions on insulin resistance in T2D patients were systematically retrieved from authoritative domestic and international databases, followed by comprehensive synthesis and analysis.ResultsTraditional meta-analyses revealed that both short-term (<12 weeks) and long-term (>12 weeks) interventions significantly improved insulin resistance and related outcomes. The exceptions included vitamin supplementation alone, which did not significantly improve glycated hemoglobin (HbA1c); neither exercise alone or vitamin supplementation alone, which failed to significantly reduce fasting blood glucose; and combined exercise interventions, which had no significant effects on insulin levels. All other interventions yielded significant benefits. Network meta-analysis revealed that, compared with the control group, probiotics provided the greatest improvement in insulin resistance. Vitamin D was most effective at improving HbA1c, whereas vitamin C had the strongest effects on fasting blood glucose and insulin indices. Dose-subgroup analysis indicated that vitamin supplementation up to 2000 IU/day most effectively reduced fasting blood glucose (p < 0.01) but had no significant effects on HbA1c or insulin (all p > 0.05). A dosage of 2,100–4,000 IU/day produced the most pronounced improvements in HbA1c (p < 0.01) and insulin (p < 0.05) but did not significantly affect insulin resistance or fasting blood glucose (all p > 0.05). Supplementation at 4100–7500 IU/day yielded the greatest improvements in insulin resistance (p < 0.01) but had no significant effect on HbA1c (p > 0.05). Exercise interventions with an intensity of ≤4 METs, performed three times per week, significantly improved insulin resistance, HbA1c, and insulin indices. Sessions lasting ≤60 min produced optimal benefits for insulin resistance and insulin measures, whereas sessions ≤45 min were most effective for HbA1c and fasting blood glucose.ConclusionVitamin supplementation at 4100–7500 IU/day combined with moderate-intensity exercise (approximately 4 METs) performed three times per week with each session lasting 45–60 min, yielded the most favorable improvements in insulin resistance and related metabolic outcomes in T2D patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250655264.